STRATEGI KOMUNIKASI BISNIS MELALUI MEDIA SOSIAL UNTUK MENINGKATKAN POTENSI DESA: (STUDI PADA DESA TAMBAKROTO, PEKALONGAN) - Isnawati, Setya Indah; Bangsa, Jaya Ramadaey; Aziz, Abdul (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
Various business sectors have started to use social media as a means of promotion as well as business development, including in developing the potential that exists in Tambakroto Village, Kajen District, Pekalongan Regency. In this village, the potentials include processing wood waste into handicrafts, containers/places for salted fish (reyeng), batik, dry land, rice fields and nature tourism. This study aims to analyze the business communication strategies carried out to increase the potential of the village. Using the descriptive analysis method, the researcher provides an overview of how business communication strategies through social media can potentially improve villages. The object of research is the community leaders of Tambakroto Village. The results of the research and discussion stated that Tambakroto Village already uses the Whatsapp and Facebook platforms to interact, and uses business communication strategies in the form of organization communication, business correspondence, specific / technical data exchange, and promotional communication. However, more efforts are still needed, namely maximizing existing social media (websites), adding Instagram and Youtube platforms and collaborating with local influencers/celebgrams/content creators.